Síntese e caracterização de vidros teluretos modificados com gadolínio - Gabriel Alexsandro de Freitas Vilhalva (2022)
In this work, telluride glasses were synthesized according to the following stoichiometric equations 80TeO2 – (20-X) LiO2 – XGd2O3 (TLGd), 20LiO2 – (80-X)TeO2 – XGd2O3 (LTGd), 75TeO2 – (25-X) LiO2 – XGd2O3 (TGdL) e 65TeO2 – (35-x) Li2O – XGd2O3 (GdTL), by the traditional method of fusion / cooling, varying the concentrations of x in 5 mol%, in order to determine a vitreous domain for this composition and investigate its properties. In the sample preparation process, it was possible to synthesize three vitreous samples, TLGd5, LTGd5 and LTGd10. For other concentrations, we obtained crystalline samples, vitro ceramic or that did not melt. FTIR measurements were made, which indicated that Gd2O3 influences and changes the characteristic of telluride glass absorption bands. With the DSC measurements, it was possible to determine characteristic temperatures for this composition. Using the Archimedes method, the densities for the vitreous samples were calculated and compared with pure telluride glasses in the literature. The Uv-vis spectrum showed us the behavior of the gap energy for these samples and the influence on the number of non-binding oxygen. Using the measured gap energy values, it was possible to use relationships to determine a theoretical value for the refractive indices of each glass sample.